PENGARUH ORIENTASI SERAT PADA KOMPOSIT RESIN POLYESTER/ SERAT DAUN NENAS TERHADAP KEKUATAN TARIK - Hendriwan Fahmi; Harry Hermansyah (Jurnal Teknik Mesin (JTM), 2011)
Pineapple leaf fiber as one of the natural fiber is currently available in high abundance, but not utilized and discarded as waste. Pineapple leaf fibers but can still be used as one alternative to natural fiber composite material. Pineapple fiber orientation variation 00, 00; 450, 00; 900to influence significantly the tensile strength of the composite. There is a maximum tensile strength with orientation 00; 450. From the results obtained using natural fibers found pineapple average of stress composite with fiber orientation 00 = 37,88 N / mm2 ,00; 450= 41,81 N /mm2, 00; 900= 39,37 N / mm2, from the results of this test we can deduce the nature of fiber reinforced resin pineapple can increase the tensile strength.